1989
DOI: 10.1007/bf00439550
|View full text |Cite
|
Sign up to set email alerts
|

Cortisol and treatment of depression: predictive value of spontaneous and suppressed cortisol levels and course of spontaneous plasma cortisol

Abstract: In 72 consecutive depressed hospitalized patients afternoon plasma cortisol was measured in three ways before treatment with antidepressants: 1) Spontaneous (n = 72), 2) 2h after oxazepam suppression (45 mg, n = 28; 60 mg, n = 37) and 3) 16 h after dexamethasone suppression (2 mg, n = 71). In addition, spontaneous cortisol was measured after 3 weeks' treatment (n = 55) and 5 weeks' treatment (n = 36). Both spontaneous and suppressed cortisol levels seemed to have a predictive value in the endogenously depresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1993
1993
2009
2009

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Other potential differences between the patients who improved and those who did not are suggested by studies of treatment-refractory depression. Patients with treatment-refractory depression have evidence of adrenergic and serotonergic disturbances (20), hypothalamic-pituitary-adrenal axis dysregulation (21)(22)(23), elevated inflammatory markers suggesting an immunological acute phase response (24,25), and low plasma folate and high homocysteine levels (26). All of these abnormalities have also been suggested as possible mechanisms underlying the effect of depression on mortality in patients with CHD (27).…”
Section: Depression and Late Mortality After MImentioning
confidence: 99%
“…Other potential differences between the patients who improved and those who did not are suggested by studies of treatment-refractory depression. Patients with treatment-refractory depression have evidence of adrenergic and serotonergic disturbances (20), hypothalamic-pituitary-adrenal axis dysregulation (21)(22)(23), elevated inflammatory markers suggesting an immunological acute phase response (24,25), and low plasma folate and high homocysteine levels (26). All of these abnormalities have also been suggested as possible mechanisms underlying the effect of depression on mortality in patients with CHD (27).…”
Section: Depression and Late Mortality After MImentioning
confidence: 99%
“…Elevated inflammatory markers consistent with an acute phase immunological response(2833), HPA axis and ANS dysregulation(3437), low thyroid hormone levels(37), and low plasma levels of omega-3 free fatty acids(38), have all been associated with poor response to a variety of antidepressants. In separate studies, they have also been identified as risk factors for cardiac morbidity and mortality.…”
Section: Inflammatory Markers and Depression Treatment Resistancementioning
confidence: 99%
“…Other findings suggest hypothalamic-pituitary-adrenal (HPA) axis hyperactivity involvement in the pathogenesis of RD. Christiansen et al (1989) found poor response to antidepressant treatment in major depressed patients with high spontaneous cortisol levels. Others (McLeod, 1972;Amsterdam et al, 1983) observed poor response to tricyclic antidepressants in patients having pathological results on the dexamethasone suppression test (DST).…”
Section: Introductionmentioning
confidence: 97%